Review of current practices and development of Islamic micro credit and micro financing - Md Saad, Norma; Abdul Razak, Dzuljastri; Abdul Rahman, Abdul Rahim (IIUM Press, 2009)
Purpose: This study aims to review the current practices of micro credit and micro financing in several Muslim countries namely Bangladesh, Pakistan, Sudan, Malaysia and Indonesia. Design/Methodology/Approach: The methodology used in this research is mainly literature review. Finding : This study found that the practices of micro credit and micro finance in Bangladesh, Malaysia and Indonesia have succeeded in alleviating poverty albeit following conventional methods. This industry is not well developed in Pakistan and Sudan as it is at its formative stage. There has not been much data found on Islamic microfinance practices with the exception of Indonesia which indicate poor performance. Implication: The study is only preliminary research and the findings of this study will hopefully provide focal areas for further research in the near future.